CITES as a tool for sustainable development - Condonier Segger, Marie-Claire; Harrington, Alexandra; Wardell, David Andrew (Treaty implementation for sustainable development, 2023)
Saving endangered species presents a critical and increasingly pressing challenge for conservation and sustainability movements, and is also matter of survival and livelihoods for the world's poorest and vulnerable communities. In 1973, a global Convention on International Trade in Endangered Species (CITES) was adopted to stem the extinction of many species. In 2015, as part of the Sustainable Development Goals (SDG 15) the United Nations called for urgent action to protect endangered species and their natural habitats. This volume focuses on the legal implementation of CITES to achieve the global SDGs. Activating interdisciplinary analysis and case studies across jurisdictions, the contributors analyse the potential for CITES to promote more sustainable development, proposing international and national regulatory innovations for implementing CITES. They consider recent innovations and key intervention points along flora and fauna value chains, advancing coherent recommendations to strengthen CITES implementation, including through the regulation of trade in endangered species globally and locally.